Implementing the partnership for Washington Square Park in downtown Kansas City, Missouri - Johnson, Chase (Kansas State University, 2014)
The use of partnerships between the public and private realm have become increasingly popular. This is due to today’s challenges of declining public resources to fulfill the social and physical needs of urban environments. This dilemma has placed a heightened emphasis on executing creative and collaborative redevelopment projects. Downtown Kansas City has an opportunity for such a project. Washington Square Park in downtown Kansas City, Missouri has a unique opportunity to stand as a catalyst project that would reconnect the urban fabric of the city, increase the population within downtown, and create an unsurpassed gateway into the greater downtown area. The public realm alone cannot accomplish this undertaking. Therefore, implementing the redevelopment of the park through public private partnerships is a natural choice. This study explores the intricacies of implementing the proposed Washington Square Park redevelopment project through the use of public private partnerships. It draws from a body of literature and precedents to provide background material, context and principles that are applied to the Washington Square Park project. The study employs site, market, and stakeholder analyses to assess the current economic environment, property ownership, power relationships and influences relating to the redevelopment project. These methods determined that as the value of Washington Square Park increases so will adjacent property; existing economic incentives are critical for project implementation; multi-family and retail real estate markets are strong while office trends are improving; current zoning allows for very high density with no height limitations; and several “key players” hold the attributes for establishing a conservancy for Washington Square Park. These findings reveal the symbiotic relationships between Washington Square Park and the surrounding context which provides the rational basis for project implementation through public private partnerships. Overall, this document informs the various stakeholders and decision-makers of pertinent information pertaining to the Washington Square Park redevelopment project and propositions a scenario for project implementation through the use of public private partnerships.
Keywords: public private partnerships; Washington Square Park; Urban Planning (0999)